Corporate Governance as a Detector of Financial Statement Fraud: Systematic Literature Review - Devi, Putu Vidya Shania (Association of Certified Fraud Examiners Indonesia Chapter, 2024)
Financial reporting fraud occurs when someone misunderstands the financial condition of a company deliberately or not. One of the causes of financial statement fraud is poor governance. This study aims to describe the development of corporate governance research as a detector of financial statement fraud. The method used in this study is Systematic Literature Review. Publish or Perish (PoP) software is used to search for articles. Based on the synthesis results, there are five corporate governance structure mechanisms that can detect financial statement fraud: auditor, board of directors, internal control, shareholders, and performance. The synthesis results show that each corporate governance structure mechanism has not been able to work together to detect financial statement fraud. Therefore, there is a need for cooperation to minimize financial statement fraud. Future research is expected to use more data to increase understanding of how companies detect financial statement fraud by accessing e-resources such as Elsevier, Springer, Emerald Insight, and Wiley. Meanwhile, Scimago can be used to assess the quality and ranking of journals.